PENGGUNAAN MEDIA BIG BOOK DALAM MENANAMKAN NILAI AGAMA DAN MORAL ANAK - Taufik, Herman; Baiti, Noor; Ratnawati (Universitas Islam Negeri Alauddin Makassar, 2022)
Religious and moral values ​​need to be instilled from an early age so that they can become the basis for developing a child's personality and character so that it can trigger a child's spiritual intelligence and interact with others with courtesy. This is formed by showing an example in a story that uses the Big Book media. This study aims to develop big book media to instill religious and moral values ​​in group B children aged 5-6 years. This study uses the Research Development (RD) method. The learning media produced is in the form of big book learning media. The techniques used are interview techniques, assessment sheets from media and material experts. The subjects of this study were 30 children in the play group. The results show that big book media can be used for teacher learning and the use of this media positively increases children's religious and moral values, with an average higher experimental class of 37.5 and a control class with an average of 20.